Penapisan Fitokimia dan Penetapan Kadar Polifenol Total Ekstrak Etanol 70% Teh Putih (Camellia sinensis L.) - Nurul Siti Aisyah; Sani Ega Priani; Gita Cahya Eka Darma (Bandung Conference Series: Pharmacy, 2024)
Abstract. White tea contains many secondary metabolites with the highest secondary metabolite compound being polyphenols. Phytochemical screening was done on alkaloid, flavonoid, polyphenol, tannin, saponin, steroid & triterpenoid, monoterpenoid & sesquiterpenoid, and anthraquinone compounds. Extraction of white tea was carried out by reflux method using 70% ethanol. The total polyphenol content contained in 70% ethanol extract of white tea was measured using the Folin-Ciocalteu method. The results showed that 70% ethanol extract of white tea contained secondary metabolites of alkaloid compounds, flavonoids, polyphenols, tannins, saponins, steroids & triterpenoids, and monoterpenoids & sesquiterpenoids. And has a total polyphenol content of 330,920 ± 4,98 mgGAE/gram or 33,092%. Abstrak. Teh putih diketahui mengandung banyak metabolit sekunder dengan senyawa metabolit sekunder paling tinggi yaitu polifenol. Penapisan fitokimia dilakukan terhadap golongan senyawa alkaloid, flavonoid, polifenol, tannin, saponin, steroid & triterpenoid, monoterpenoid & seskuiterpenoid, dan antrakuinon. Ekstraksi teh putih dilakukan dengan metode refluks menggunakan etanol 70%. Kemudian kadar polifenol total yang terkandung dalam ekstrak 70% etanol teh putih diukur menggunakan metode Folin-Ciocalteu. Hasil penelitian menunjukan ekstrak etanol 70% teh putih mengandung metabolit sekunder senyawa alkaloid, flavonoid, polifenol, tannin, saponin, steroid & triterpenoid, dan monoterpenoid & seskuiterpenoid. Serta memiliki kadar polifenol total sebesar 330,920 ± 4,98 mgGAE/gram atau sebesar 33,092%.